ANALYSIS OF TECHNOLOGY FOR REDUCTION OF DUST POLLUTION IN COTTON CLEANING INDUSTRIES - Turgunov , D.U.; Egamberdiyev, A.B. (Educational Research in Universal Sciences, 2023)
The main scientific and technical issue of creating a dust collector with small hydraulic resistance and implementing an optimal scheme of dust cleaning based on the acceleration of the device for capturing dust from the air in cotton gins and light industrial enterprises is studied in the following article.